Kreativitas Rd. Tjetje Somantri dalam Tari Puja - Mulyani, Ai; Rosilawati, Riyana (LP2M ISBI Bandung, 2020)
ABSTRACTThe Puja dance is the product of Raden Tjetje Somantri’s creativity, in which there is a touch of SundanesePriyayi culture and Javanese dance. The dance is included in the classic Sundanese dance. This paperintends to examine how creativity Rd. Tjetje Somantri in the Puja dance. The method used is qualitativewith a descriptive analysis approach, namely through observation, in-depth interviews, and parentalobservation. From the analysis it is known that there is a touch of Javanese culture that has been going onfor a long time, and the influence of Javanese culture which is identified with the behavior of ‘alus’ moreinfluences Sundanese style dance Rd. Tjetje Somantri. This alus culture originates from the concept ofprijaji which is symbolized by a gentle behavior called ‘alus’. Some Sundanese dances influenced by ‘alus’culture include the Puja style Rd.Tjetje Somantri style. The result of creativity there is also a pattern ofrelationships that occur from the touch, namely 1) Cooperation that is marked by contact between ethnicJavanese and Sundanese, and competition in terms of creating dance works of art. The results obtainedshow the Puja Gaya Rd.Tjetje dance from the intact choreography aspects of Javanese dance, Sundanesedance techniques and styles.Keywords: Creativity, Puja dance, Rd.Tjetje SomantriABSTRAKTari Puja merupakan hasil kreativitas Rd. Tjetje Somantri, yang di dalamnya terdapat sentuhanbudaya Priyayi Sunda dan Tari Jawa. Tarian tersebut termasuk dalam Tari Sunda Klasik.Tulisan ini bermaksud untuk mengkaji bagaimana kreativitas Rd. Tjetje Somantri dalam tariPuja. Metode yang digunakan kualitatif dengan pendekatan deskriptif analisis yaitu melaluipengamatan, wawancara mendalam, dan observasi parsitipan. Dari hasil analisa diketahuiadanya sentuhan budaya Jawa sudah berlangsung lama, dan pengaruh budaya Jawa yangdiidentikkan dengan perilaku alus lebih banyak mempengaruhi tarian sunda gaya Rd. TjetjeSomantri. Budaya alus ini berasal dari konsep priyayi yang disimbolkan dengan perilaku yanglemah lembut yang disebut alus. Beberapa tarian Sunda yang dipengaruhi budaya alus diantaranya Tari Puja gaya Rd.Tjetje Somantri. Hasil dari kreativitas terdapat juga pola hubunganyang terjadi dari sentuhan tersebut, yakni 1) Kerjasama yang ditandai adanya kontak antaraetnis Jawa dan etnis Sunda, dan kompetisi yaitu dalam hal menciptakan karya-karya seni tari.Hasil penelitian yang diperoleh menunjukkan Tari Puja Gaya Rd.Tjetje dari aspek koreografiutuh Tari Jawa, teknik dan gaya Tari Sunda.Kata Kunci: Kreativitas, Tari Puja, Rd.Tjetje Somantri